Enhanced Myogenic Constriction in the SHR Preglomerular Vessels Is Mediated by Thromboxane A2 Synthesis - Nademi, Samera; Lu, Chao; Dickhout, Jeffrey G. (Frontiers in Physiology, 2020)
Background Spontaneously Hypertensive Rats (SHR) have chronically elevated blood pressures at 30 weeks of age (systolic: 191.0 ± 1.0, diastolic: 128.8 ±0.9). However, despite this chronic malignant hypertension, SHR kidneys remain relatively free of pathology due to having an augmented myogenic constriction (MC). We hypothesized that the enhanced MC in the SHR preglomerular vessels was due to increased prostaglandin and decreased nitric oxide (NO) synthesis, providing renal protection. Methods SHR and Wistar Kyoto (WKY) arcuate and mesenteric arteries were treated with indomethacin (prostaglandin synthesis inhibitor), N omega-nitro-L-arginine (L-NNA, nitric oxide synthase inhibitor), and nifedipine (L-type calcium channel blocker); and MC was measured in these vessels. The role of endothelium in MC was examined by removing endothelium from WKY and SHR preglomerular and mesenteric arteries using human hair, and measuring MC. We also studied the source of prostaglandin in the SHR by treating endothelium-removed arcuate arteries with indomethacin and furegrelate (thromboxane synthase inhibitor). Results MC was enhanced in the SHR preglomerular vessels but not the mesenteric arteries. Indomethacin and LNNA removed the enhanced MC in the SHR. Nifedipine also inhibited MC in both WKY and SHR arcuate and mesenteric arteries. Removing endothelium did not change MC in either arcuate or mesenteric arteries of WKY and SHR rats; and did not remove the augmented MC in the SHR arcuate arteries. Indomethacin and furegrelate decreased MC in endothelium-removed SHR arcuate arteries and obliterated the enhanced MC in the SHR. Conclusions The enhanced MC in the SHR arcuate arteries was due to thromboxane A2 synthesis from the tunica media and/or adventitia layers. MC was not dependent on endothelium, but was dependent on L-type calcium channels. Nevertheless, SHR arcuate arteries displayed differential intracellular calcium signalling compared to the WKYs.